Assessment of children’s health and indoor air contaminants of day care centre in industrial area - Cionita, Tezara; Jalaludin, Juliana; Adam, Nor Mariah; Siregar, Januar Parlaungan (Tehran University of Medical Sciences, Tehran, Iran, 2014)
Background: Carbon dioxide (CO2) is one of the most commonly used indicators of indoor air quality (IAQ) in industrial area. The higher concentration level of CO2 and particulate matter (PM10) in day care centre could affect children’s health. The objective of this study was to assess children’s health symptom, and measure the CO2 and PM10 concentration level as IAQ parameters in different locations of day care centres near the industrial area at Kuala Lumpur, Selangor and Hulu Langat as urban, suburban and rural areas respectively.